THE EFFECT OF USING CLUSTERING TECHNIQUE ON THE STUDENTS ACHIEVEMENT IN WRITING RECOUNT TEXT - Kiki Elista; Riska Evangelina Hutabarat; Jefri Ricardo Doloksaribu; Desiana Bondar (elt, 2020)
ABSTRACT This research was conducted to investigate the effect of using clustering techniques on the student achievement in writing recount text. Therefore, an experimental research was conducted to obtain the data, the population of this study were the first school year in the academic year 2019/2020 of SMA DHARMAWANGSA Medan which has two classes consisted of 80 students. They were taken as the sample. 40 students in the experimental group were taught using clustering techniques while the other 40 students in the control group were taught using free writing technique. Writing test was used to acquire to obtain data. The result the data analyzing indicated that there is a large effect of using clustering technique on the students’ achievement in writing recount text since the result tobserved> ttable or 2.568 > 2.06. Thus, the null hypothesis is rejected while the alternate hypothesis is accepted. This the student who are taught using clustering technique could achieve better achievement than students who were taught rewriting technique. Result of data analyzing suggests that teachers should consider the use of clustering techniques in writing recount text to their students. Keyword : Writing , Recount Text , Clustering Technique